Industry Structure, Bank Adequacy, Operational Efficiency: Financial Performance Applied Study on the Islamic Banks Listed in Bahrain Stock Exchange - Shaalan, Tharwah (International Journal of Economics and Financial Issues, 2019)
The purpose of this study is to test the relationship between the market power variables and the bank concentration of Islamic banks registered in Bahrain Stock Exchange, using the HHI index of loans, in addition to other variables such as bank solvency, operational efficiency and financial leverage on the financial performance of these banks, which are represented by the return on assets and the efficiency of lending profitability using regression data panel analysis. To test the hypotheses of this study, the researcher employed the multiple regression method as well as the same using the panel data. The results of this applied study determined a fundamental impact exerted by the bank’s capital adequacy and market share on the rate of return on assets as well as the intrinsic effect of operational efficiency variables and bank concentration to contribute to the efficiency variable of lending to these banks. Keywords: Islamic banks, bank performance, financial performance, market power, market concentration. JEL Classifications: C23, G21, L11 DOI: https://doi.org/10.32479/ijefi.7452